Kelimpahan Mamalia di Dusun Oelmuke Kecamatan Mutis Kabupaten Timor Tengah Utara - Gonsianus Pakaenoni (Saintek Lahan Kering, 2019)
Mammals are the highest group of animals in the animal kingdom, and are one of the classes of vertebrate animals that are characterized by hair and mammary glands (mammary glands). Research records regarding the abundance of mammals in Oelmuke Hamlet to date are 0%. The study of the abundance of mammal species is very important to do, because it can produce basic data that can be used as a guide to find out the abundance of mammals in the area under study. Therefore it is necessary to study the abundance of individual mammal species found in the Oelmuke Village area as preliminary data on the abundance of mammal species in the region. This research was carried out in Oelmuke Village, Mutis District, North Central Timor Regency in August 2019 with direct observation using strip transect method. The results showed that four types of mammals were found in the T01-Ta1 and T02-Ta2 observation pathways, consisting of 30 individual pigs (Sus scrofa domesticus), 37 individual cows (Bos indicus), 17 dogs (Canis lupus), and 20 individual horses (Equus caballus). The largest diversity index value of mammals is Bos indicus on the T01 - Ta1 observation pathway with an H 'value of 0.1598 and the lowest is Canis lupus on the T01 - Ta1 observation pathway with an H' value equal to 0.1236. Mammalian species evenness index values on all observation pathways (T01-Ta1 and T02-Ta2) ranged from 0.1190 to 0.1491. The value of mammalian species wealth index in the T01-Ta1 observation lane was 4.2592 and the mammal species wealth index on the T02-Ta2 lane was 11.8097. The highest index value of abundance of mammals was found in cows (Bos indicus) of 36.67%, and the lowest index value of abundance of mammals was found in dogs (Canis lupus) of 15.00%. To facilitate further research, it is necessary to compile a biodiversity database and inventory activities for each animal species in a certain area should also be improved.